The Concept of Gynecologic Oncology Services in Jakarta Related to Academic Health System - Purbadi, Sigit (Indonesian Socety of Obstetrics and Gynecology, 2017)
An Academic Health System (AHS) is a system in partnership among universities and health care providers that focuses on education, training, service, and research. The final outcome of this partnership is to improve health status. Numerous countries have been using this system, since this system is proven to lead to better sustainable outcome.The vision of Faculty of Medicine, University of Indonesia (FMUI) is